ANALISIS HUBUNGAN MAKNA KANJI BER-BUSHU SANZUI HEN (æ°µ) DENGAN ARTI AIR DALAM KATEGORI KATA KERJA JOUYOU KANJI - Adis Kusumawati (Universitas Airlangga, 2020)
This study examines to analyze the relation between the meaning of kanji and kanji bushu.This research uses Joyo Kanji newest revised edition of 2010 as the source of data. Collected from the joyo kanji, the type that is used are the verbs class category of kanji bushu sanzui hen. The scientific method used in this research is descriptive qualitative method. The data is analayzed concerning the semantic meaning descriptively. As the result of this research, 42 kanji bushu sanzui hen is found that is categorized as verb that is formed of 25 kanji that have correlation with water meaning and 17 kanji do not have relation with the water meaning. The semantic roles found in this research are location, patient, theme, agent, instrument and source. Particles that follows the words correlated to the water meaning by definition, have an important role to show how the relation of bushu sanzui hen with the meaning.